The superior thyroid artery origin pattern: a systematic review with meta-analysis. - Triantafyllou, George; Paschopoulos, Ioannis; Duparc, Fabrice; Tsakotos, George; Tsiouris, Christos; Olewnik, Łukasz; Georgiev, Georgi; Zielinska, Nicol; Piagkou, Maria (Surgical & Radiologic Anatomy, 2024)
Purpose: The current systematic review with meta-analysis aimed to investigate the pooled prevalence of the superior thyroid artery (STA) pattern of origin (distinct or fused-common origin with adjacent arteries in the form of a common trunk). The standard and uncommon variants were also studied, considering the STA's exact surface of origin and the relationship with the upper border of the thyroid cartilage (TC, reference point), considering the laterality effect. Thus, the STA topographical anatomy was considered. Methods: An evidence-based systematic review with meta-analysis was performed according to the PRISMA 2020 guidelines. A literature search was conducted in four online databases using specific keywords, the pooled prevalence was calculated using statistical analysis in the R programming language, and multiple subgroup analyses were performed. Results: The most common distinct origin of the STA was from the external carotid artery (ECA) (56.94% pooled prevalence, 95%CI: 50.89–62.89), and the rarest one was from the internal carotid artery (ICA) (< 0.01%, 95%CI: 0.00–0.00). Common trunks were also investigated, with the thyrolingual trunk emanating from the ECA estimated at 0.61% (95%CI: 0.21–1.14), representing the most common. Subgroup analysis based on the nationality, type of study, and sample size, as well as a comparison between left and right sides and males and females, were investigated. Conclusions: The most common STA origin was estimated as the ECA, the medial surface of origin, and above the TC upper border. Adequate knowledge of STA origin is paramount for surgeons, especially during thyroidectomy, not to cause iatrogenic injury to the external branch of the superior laryngeal nerve.